Association between QRS Duration and Obstructive Sleep Apnea - Gupta, Shuchita (American Academy of Sleep Medicine, 2012)
BACKGROUND: Both obstructive sleep apnea (OSA) and prolonged QRS duration are associated with hypertension, heart failure, and sudden cardiac death. However, possible links between QRS duration and OSA have not been explored. METHODS: Cross-sectional study of 221 patients who underwent polysomnography at our center. Demographics, cardiovascular risk factors and ECG were collected to explore a relationship between OSA and QRS duration. RESULTS: The apnea-hypopnea index (AHI) was positively correlated with QRS duration (r = 0.141, p = 0.03). Patients were divided into 3 groups: AHI < 5 (61), AHI 5-29 (104), and AHI > 30 (55). The mean QRS duration prolonged significantly as OSA worsened (AHI < 5, 85 ± 9.5; AHI 5-29, 89 ± 11.9; and AHI > 30, 95 ± 19.9 ms, p = 0.001). QRS ≥ 100 ms was present in 12.7% of patients with severe OSA compared with 0% in the rest of the sample (p < 0.0001). After adjustment for age, race, and cardiovascular risk factors, this association remained significant in women but not in men. CONCLUSION: QRS duration and OSA were significantly associated. Severity of OSA independently predicted prolonged QRS in women but not men. Nevertheless, prolongation of QRS duration in either sex may potentiate arrhythmic risks associated with OSA. CITATION: Gupta S; Cepeda-Valery B; Romero-Corral A; Shamsuzzaman A; Somers VK; Pressman GS. Association between QRS duration and obstructive sleep apnea. J Clin Sleep Med 2012;8(6):649-654.